2023
DOI: 10.1145/3592624
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Inverse Transparency with Blockchain

Abstract: Employee data can be used to facilitate work, but their misusage may pose risks for individuals. Inverse transparency therefore aims to track all usages of personal data, allowing individuals to monitor them to ensure accountability for potential misusage. This necessitates a trusted log to establish an agreed-upon and non-repudiable timeline of events. The unique properties of blockchain facilitate this by providing immutability and availability. For power asymmetric environments such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
0
0
Order By: Relevance
“…For example, in our research we found existing solutions based on trusted computing modules [see, e.g., 1, 52, 67], cryptographically secured protocols such as forwardsecure authentication [see, e.g., 3,41,55], or distributed ledger technology, i.e. blockchain [see, e.g., 33,77,97]. Recent challenges seem to include heterogeneity of hardware [52] and GDPR compliance, especially considering the right to erasure [96].…”
Section: Usage Log Integritymentioning
confidence: 99%
“…For example, in our research we found existing solutions based on trusted computing modules [see, e.g., 1, 52, 67], cryptographically secured protocols such as forwardsecure authentication [see, e.g., 3,41,55], or distributed ledger technology, i.e. blockchain [see, e.g., 33,77,97]. Recent challenges seem to include heterogeneity of hardware [52] and GDPR compliance, especially considering the right to erasure [96].…”
Section: Usage Log Integritymentioning
confidence: 99%